Earnings management and firm valuation under asymmetric information - Chaney, Paul K.; Lewis, Craig M. (Journal of Corporate Finance, 1995)
This paper seeks to provide an explanation for why corporate officers manage the disclosure of accounting information. We show that earnings management affects firm value when value-maximizing managers and investors are asymmetrically informed. In equilibrium, the strategic management of reported earnings influences investors' assessments of the market values of companies' shares.